A new protein tyrosine phosphatase 1B inhibitory α-pyrone-type polyketide from Okinawan plant-associated Aspergillus sp. TMPU1623. (August 2018) - Yamazaki, Hiroyuki; Takahashi, Kenta; Iwakura, Natsuki; Abe, Tatsuki; Akaishi, Masanari; Chiba, Satomi; Namikoshi, Michio; Uchida, Ryuji
Abstract A new polyenyl-α-pyrone polyketide, aspopyrone A (1 ), was isolated from a culture broth of Okinawan plant-associatedAspergillus sp. TMPU1623 by solvent extraction, ODS column chromatography, and preparative HPLC (ODS). The structure of1 was assigned based on NMR experiments. Compound1 exhibited protein tyrosine phosphatase (PTP) 1B and T-cell PTP (TCPTP) inhibitory activities with IC50 values of 6.7 and 6.0 μM, respectively.